2012
DOI: 10.1261/rna.031120.111
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive evaluation of canonical versus Dicer-substrate siRNA in vitro and in vivo

Abstract: Since the discovery of RNA interference (RNAi), researchers have identified a variety of small interfering RNA (siRNA) structures that demonstrate the ability to silence gene expression through the classical RISC-mediated mechanism. One such structure, termed ''Dicer-substrate siRNA'' (dsiRNA), was proposed to have enhanced potency via RISC-mediated gene silencing, although a comprehensive comparison of canonical siRNAs and dsiRNAs remains to be described. The present study evaluates the in vitro and in vivo a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 32 publications
1
40
1
Order By: Relevance
“…not draw conclusions on the frequency of sequences that would benefit from longer -27/29 and -29/31 dsiRNA formats. However, our results suggest that conflicting conclusions reported by Foster et al, showing no benefit of dsiRNAs in gene silencing (19), may have been a result of the -25/27 format used rather than the dsiRNA concept itself. For the Gag 1498 target site, our results demonstrate that dsiRNAs with a sense strand length of at least 27 nt provide the greatest potency and efficacy against HIV-1 production compared to shorter siRNAs.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…not draw conclusions on the frequency of sequences that would benefit from longer -27/29 and -29/31 dsiRNA formats. However, our results suggest that conflicting conclusions reported by Foster et al, showing no benefit of dsiRNAs in gene silencing (19), may have been a result of the -25/27 format used rather than the dsiRNA concept itself. For the Gag 1498 target site, our results demonstrate that dsiRNAs with a sense strand length of at least 27 nt provide the greatest potency and efficacy against HIV-1 production compared to shorter siRNAs.…”
Section: Discussioncontrasting
confidence: 81%
“…This format helps direct Dicer to process the desired canonical siRNA product (16,17) and results in better RISC assembly and more loading of the antisense strand into Ago proteins than canonical designs (18). Although several reports have observed superior efficacy of dsiRNAs over that of canonical siRNAs, one study reported no major difference in efficacy between a large set of molecules and provided evidence that dsiRNAs have greater effects on cell viability (19). In another study, dsiRNAs were shown to have major effects on cell viability in DU145, MCF7, and HeLa S3 cells compared to those of canonical designs (20).…”
mentioning
confidence: 99%
“…This requirement for any kind of RNAi therapeutic stems from the transient nature of gene silencing effects (typically on the order of several days to several weeks in vivo ) and the subsequent need for sustained, repeated siRNA dosing over the course of treatment 10,11 . Unfortunately, improvements in delivery vehicle potency do not always result in an enlargement of the therapeutic index due to reductions in tolerated dose levels.…”
Section: Introductionmentioning
confidence: 99%
“…1) [17,27]. It has been routinely used as an alternative for detection of mRNA expression and siRNA efficacy in cell culture assays for the past decade [15,[17][18][19][20][21]. Here, we evaluated the merit of using the bDNA assay for detecting mRNA expression directly from tissue biopsies, by using the automatic TissueLyser II (Qiagen) for tissue homogenization, followed with direct detection of mRNA levels by bDNA (see Materials and Methods for experimental details).…”
Section: Resultsmentioning
confidence: 99%
“…This method utilizes a plate-based, luminescent assay to directly assess the amount of mRNA in 96 samples simultaneously, without the need to isolate RNA or include a standard curve [17]. It has been used routinely for diagnostics, and to a lesser extent, to assess the efficacy of oligonucleotides in vivo [15,[17][18][19][20][21]. A previous report compared qRT-PCR to the QuantiGene assay and determined that QuantiGene has a better linear range and relative accuracy versus qRT-PCR [22].…”
mentioning
confidence: 99%